Impact of SGBs’ Language Policy Decisions on Language of Instruction in Primary Schools in Hammanskraal - Makgabo, Mmamoyahabo Constance; Modise, Penelope M. (JOLLT Journal of Languages and Language Teaching, 2026)
This study examines the consequences of School Governing Bodies’ (SGBs) decisions regarding the Language of Learning and Teaching (LoLT) in primary schools in Hammanskraal, a linguistically diverse context where most learners are not home-language speakers of English. Despite extensive evidence supporting mother-tongue-based education, SGBs continue to prioritise English as the medium of instruction. Anchored in a qualitative interpretive paradigm, the study draws on semi-structured interviews with SGB members, classroom observations, and document analysis of learners’ written work. Vygotsky’s sociocultural theory and Piaget’s cognitive development theory frame the analysis, highlighting the central role of language in cognitive development and meaning-making. The findings reveal that English-medium instruction, when introduced without sufficient linguistic scaffolding, leads to difficulties in comprehension, participation, and vocabulary acquisition, as well as subject-specific language, particularly in conceptually demanding subjects such as the Natural Sciences. Teachers often resort to code-switching, underscoring the continued relevance of the mother tongue. The study further demonstrates a misalignment between language policy, governance decisions, and classroom realities. Furthermore, it contributes to broader debates on English-medium instruction in multilingual contexts and provides evidence-based insights to inform language policy reform, including the implementation of the Basic Education Laws Amendment (BELA) Act. Finally, the study recommends an additive bilingual approach that balances mother-tongue instruction with the gradual development of English academic proficiency to promote equitable educational outcomes.